(untitled) (Fiep Bulletin - online, 2013)
During my education I could identify the need to relate classical ballet with the area of physical education. This study seeks to identify the representations of body and dance in the film Black Swan at the prospect of young dancers, and then analyze the classical ballet as possible learning content in school physical education classes. Was applied an interview with ten young dancers, aged between 14 and 18 years. All belong to a gym / school of classical ballet in the city of Rio de Janeiro. With literature reviews about topics like social imaginary, representation of the body, dance and physical education, was obtained foundations that collaborated with basic information and theoretical proposal for discussion in the study. The results from the interviews will be approached with the main ideas proposed by the movie Black Swan, and reversed the interpretation in the light of the literature review presented in the work. So that was a reflection on the teaching of classical ballet as a possible curriculum in physical education classes. Thus, with the data extracted from the survey, we highlight some items that may be relevant to work for classical ballet with students in the classroom.